Diversity of Endolysin Domain Architectures in Bacteriophages Infecting Bacilli - Olga N. Koposova; Olesya A. Kazantseva; Andrey M. Shadrin (Biomolecules)
The increasing number of antibiotic-resistant bacterial pathogens is a serious problem in medicine. Endolysins are bacteriolytic enzymes of bacteriophages, and a promising group of enzymes with antibacterial properties. Endolysins of bacteriophages infecting Gram-positive bacteria have a modular domain organization. This feature can be used to design enzymes with new or improved properties by modifying or shuffling individual domains. This work is a detailed analysis 1of the diversity of endolysin domains found in bacteriophages infecting bacilli. During the course of the work, a database of endolysins of such bacteriophages was created, and their domain structures were analyzed using the NCBI database, RASTtk, BLASTp, HHpred, and InterPro programs. A phylogenetic analysis of endolysins was performed using MEGA X. In 438 phage genomes, 454 genes of endolysins were found. In the endolysin sequences found, eight different types of catalytic domains and seven types of cell wall binding domains were identified. The analysis showed that many types of endolysin domains have not yet been characterized experimentally. Studies of the properties of such domains will help to reveal the potential of endolysins for the creation of new antibacterial agents.